2023
DOI: 10.2147/ijn.s396087
|View full text |Cite
|
Sign up to set email alerts
|

ROS-responsive Galactosylated-nanoparticles with Doxorubicin Entrapment for Triple Negative Breast Cancer Therapy

Abstract: Background Triple negative breast cancer (TNBC) is one of the most aggressive tumors with high metastasis and mortality, which constitutes 15~20% of all breast cancers. Chemotherapy remains main therapeutic option in the treatment of patients with TNBC. Methods We developed reactive oxygen species (ROS)-responsive galactosylated nanoparticles (DOX@NPs) as an efficiently targeted carrier for doxorubicin (DOX) delivery to inhibit the growth of TNBC in vitro and in vivo. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Compared with many previous drug delivery platforms that can only retard the growth of tumors, our results underscore the favorable outcome of the synergistic application of chemotherapy and PTT in tumor treatment. 60 , 61 Multimodal therapy, in comparison to chemotherapy alone, exhibited a significantly enhanced tumor eradication effect.
Figure 7 In vivo antitumor assay.
…”
Section: Resultsmentioning
confidence: 98%
“…Compared with many previous drug delivery platforms that can only retard the growth of tumors, our results underscore the favorable outcome of the synergistic application of chemotherapy and PTT in tumor treatment. 60 , 61 Multimodal therapy, in comparison to chemotherapy alone, exhibited a significantly enhanced tumor eradication effect.
Figure 7 In vivo antitumor assay.
…”
Section: Resultsmentioning
confidence: 98%
“…4T-1, NF639, EO771, MDA-MB-231, and MCF-7 cells (1 × 10 4 /well) were seeded in 96-well plates, treated with XK-81 at 5, 10, 15, and 20 µM concentrations for 0 h, 12 h, 24 h, and 48 h, respectively. Additionally, then the diluted MTT solution was added, and the reaction lasted for 4 h. The culture medium was removed, and DMSO was added to dissolve the reaction, forming formazan, and the absorbance was measured immediately after blending [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Animal experiments demonstrated that the system had potent pro-apoptotic, anti-metastatic and anti-angiogenic effects, thus exerting potent TNBC efficacy. Zhou et al ( Zhou et al, 2023 ) developed a ROS-responsive chemo-nanoparticles from galactose-conjugated phenylboronic acid for effective targeted delivery of DOX (DOX@NPs). It was found that DOX could be rapidly released under 1 mM H 2 O 2 medium conditions, and its cumulative release of DOX for 24 h could reach 60%.…”
Section: Novel Nano-drug Delivery Systemsmentioning
confidence: 99%
“… (A) Schematic diagram of the preparation and biodistribution of ROS responsiveness DOX@NPs and evaluation of its antitumor activity ( Zhou et al, 2023 ). Copyright 2023.…”
Section: Novel Nano-drug Delivery Systemsmentioning
confidence: 99%